The Contribution of Surface Tension-Dependent Alveolar Septal Stress Concentrations to Ventilation-Induced Lung Injury in the Acute Respiratory Distress Syndrome - Perlman, Carrie E. (Frontiers in Physiology, 2020)
In the acute respiratory distress syndrome (ARDS), surface tension, T, is likely elevated. And mechanical ventilation of ARDS patients causes ventilation-induced lung injury (VILI), which is believed to be proportional to T. However the mechanisms through which elevated T may contribute to VILI have been under-studied. This conceptual analysis considers experimental and theoretical evidence for static and dynamic mechanical mechanisms, at the alveolar scale, through which elevated T exacerbates VILI; potential causes of elevated T in ARDS; and T-dependent means of reducing VILI. In the last section, possible means of reducing T and improving the efficacy of recruitment maneuvers during mechanical ventilation of ARDS patients are discussed.